Implementing the PBL Model to Improve Students' Mathematical Problem Solving Ability at Medan State Junior High School - Dian Anjeli Siregar; Denny Haris; Hasiholan Sitompul (Study Program of Mathematics Education of Unimed Postgraduate Program, 2023)
This study aims to find out: (1) what efforts are being made to improve the mathematical problem-solving skills of students in class XI, IPS 1, of Medan 7 State Senior High School through a problem-based learning model; and (2) how to improve students' mathematical problem-solving skills in class XI, IPS 1, of Medan 7 State Senior High School after applying the problem-based learning model. This type of research is called